German Readers’ Perception of Uzbek Culture Through the Translation of “Bygone Days” (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines how German readers perceive Uzbek culture through the German translation of Abdulla Qodiriy’s Bygone Days (O‘tkan kunlar), the first Uzbek novel published in 1926. By analyzing the translation’s linguistic and cultural mediation, the study explores the challenges of conveying Uzbek cultural nuances to a German audience and how these shape readers’ understanding of Uzbek identity, traditions, and historical context. Drawing on translation studies, reader-response theory, and linguo-culturology, the article employs a comparative analysis of translations by Arno Specht (1968) and Barno Aripova (2020), supplemented and revised using the original and qualitative data from German reader reviews. It is noteworthy that Arno Specht retitled the translation of the novel as “die liebenden von Taschkent” (the lovers of Tashkent). Findings suggest that while translations successfully introduce Uzbek cultural elements, certain nuances, such as idiomatic expressions and historical references, are partially lost, influencing readers’ perceptions. The article highlights the translator’s role as a cultural mediator and proposes strategies for enhancing cross-cultural understanding.